Cutting Off Functional Loops from Homodimeric Enzyme Superoxide Dismutase 1 (SOD1) Leaves Monomeric β-Barrels - Danielsson, Jens (American Society for Biochemistry and Molecular Biology, 2011)
Demetallation of the homodimeric enzyme Cu/Zn-superoxide dismutase (SOD1) is known to unleash pronounced dynamic motions in the long active-site loops that comprise almost a third of the folded structure. The resulting apo species, which shows increased propensity to aggregate, stands out as the prime disease precursor in amyotrophic lateral sclerosis (ALS). Even so, the detailed structural properties of the apoSOD1 framework have remained elusive and controversial. In this study, we examine the structural interplay between the central apoSOD1 barrel and the active-site loops by simply cutting them off; loops IV and VII were substituted with short Gly-Ala-Gly linkers. The results show that loop removal breaks the dimer interface and leads to soluble, monomeric β-barrels with high structural integrity. NMR-detected nuclear Overhauser effects are found between all of the constituent β-strands, confirming ordered interactions across the whole barrel. Moreover, the breathing motions of the SOD1 barrel are overall insensitive to loop removal and yield hydrogen/deuterium protection factors typical for cooperatively folded proteins (i.e. the active-site loops act as a “bolt-on” domain with little dynamic influence on its structural foundation). The sole exceptions are the relatively low protection factors in β-strand 5 and the turn around Gly-93, a hot spot for ALS-provoking mutations, which decrease even further upon loop removal. Taken together, these data suggest that the cytotoxic function of apoSOD1 does not emerge from its folded ground state but from a high energy intermediate or even from the denatured ensemble.